TERRITORIAL DEVELOPMENT AS A PRIORITY DIRECTION OF THE STATE REGIONAL POLICY - Voronina Ю.; Plotnichenko С. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The article studies the state of the territory development. The authors consider the state regional policy as one of the priority areas of territorial development, the purpose of which is to create appropriate conditions for the dynamic, balanced socio-economic development of Ukraine and its regions, to raise the standard of living of the population, to ensure compliance with state-guaranteed social protection for each of its citizens regardless the place of residence. Thus, effective development of each economic system requires a constant search for optimal options to combine the state and market components and interests. To ensure sustainable economic, social and ecological development of various regions of the country, the state should pay much attention to the development of territories. At the current stage of the market relations development, the problem of socio-economic development takes a decisive position in the general strategy of the country development. At the same time, the regional level headed by local authorities, which are actually responsible for the economic situation in the country, is the center of main transformations. Today, there is a number of problems in the field of local self-government, which together effect the macroeconomic situation in the country. The main tasks of the regional policy as to ensuring a balanced development of all regions of the country are analyzed in the paper. To achieve these goals, the state regional policy should include a wide range of measures that will contribute to development of territories, such as investment support, infrastructure development, advanced training of the workforce, support for small and medium-sized businesses, innovative technologies, etc. It is clear that the successful development of territories requires not only the proper attention of the state, but also involvement of the public in the process of making decisions concerning the region development. Regional cooperation between different regions of the country and international partnerships are also an important factor. It is substantiated that in the context of globalization and rapid changes in economic conditions, development of territories has become an important element of sustainability and competitiveness.